PERGESERAN MITOLOGI JILBAB (Dari Simbol Status ke Simbol Kesalehan/Keimanan) - Safri, Arif Nuh (Musawa Jurnal Studi Gender dan Islam, 2014)
The problem of the veil remains a controversial issue that requires ongoing debate. This is inevitable becauseÂ  the use or wearing of a veil is closely associated with culture. In terms of etymology, the term hijab was not known in Indonesia until the coming of Islam. In the history of Indonesia, females are more familiar with the term kerudung than jilbab (both meaning veil). In the contemporary era, however, the term jilbab is arguably also marginalized by the term hijab. This word shift must have been influenced by the local culture. If the term can shift, so too can the meaning of its functions and benefits. Through this article, the author tries to read the veil from its shifting meanings and functions. For Roland Barthes the shift in meaning is called myth. It is very interesting to present the veil from the perspective of mythology, so that at a glance we can see the shift in the meaning of the veil in the Muslim community, ranging from a status symbol from the pre-Islamic era to the time of the Prophet, and now to a symbol of piety andÂ  lifestyle.